Preconditioning of Mesenchymal Stem Cells with Non-ToxicConcentration of Hydrogen Peroxide Against Oxidative StressInduced Cell Death: The Role of Hypoxia-Inducible Factor-1 - Fatemeh Nouri; Seyed Noureddin Nematollahi-Mahani; Ali Mohammad Shariﬁ (Tabriz University of Medical Sciences, 2019)
Purpose: To investigate the protective effect of preconditioning with non-toxic dose of hydrogenperoxide (H2O2) as a possible cell signaling molecule, against cell death induced by toxicconcentration of H2O2 or by serum deprivation in human Wharton's jelly-derived mesenchymalstem cells (HWJ-MSCs) and underlying mechanisms.Methods: HWJ-MSCs were isolated and identified using flow cytometry. After finding non-toxicconcentration of H2O2, cells preconditioning was performed by H2O2 (20 μM) for 12 h and celltolerance against serum deprivation or toxic levels of H2O2 was assayed by MTT test. Effect ofpreconditioning on mRNA and protein expression of Akt-1, Bcl-2 and Bax were examined usingreverse transcription polymerase chain reaction (RT-PCR) and western blotting respectively. Roleof hypoxia-inducible factor (HIF)-1α was explored in presence HIF-1α inhibitor.Results: Preconditioning with 20 μM H2O2 for 12 h was non-toxic and decreased cell deathinduced by oxidative stress and serum deprivation in MSC cultures. However, the increasedtolerance reversed in the presence of inhibitor of HIF-1α. By regards to RT-PCR and westernblotting data, although expression of Akt-1, Bcl-2 and Bax was not change considerably butphosphorylated Akt-1 (pAkt-1) was up regulated after treatment with 20 μM H2O2 compared tocontrol group. Moreover after exposure to 100 μM H2O2, western blotting analysis showed thatcell pretreatment with 20 μM H2O2, decremented Bax/Bcl2 ratio and up-regulated HIF-1α andpAkt-1 compared to the control group.Conclusion: Increased tolerance of H2O2-pretreated cells led to the suggestion that transplantationof H2O2 preconditioned MSCs may improve therapeutic potential of stem cells in cell therapyprocedures.